Comparison between MEKC and UV spectral deconvolution to follow sorption experiment in soil - Lima, Diana L. D.
In this study a simple and rapid procedure for monitoring sorption of atrazine onto soil samples was developed This method is based on a multiwavelength UV spectral deconvolution (UVSD) where the UV spectrum of a sample is considered as a linear combination of absorption spectra, named reference spectra. The combination of the reference spectra allows the restitution of the shape of the UV spectrum of any unknown sample. In order to evaluate the accuracy of this method, a sorption study of atrazine to three different soil samples was monitored using both UVSD and micellar electrokinetic chromatography (MEKC) methods The Freundlich parameters (K(F) and N) obtained for all soil samples tested were similar for both methods and UVSD has proven to be an accurate methodology, since the results did not present statistical significant differences at 95% confidence level Moreover, the LOD obtained using UVSD presented lower values (0 066-0.12 mg L(-1)) than the one obtained using MEKC (0.26 mg L(-1)) The proposed UVSD method has been proven useful as a valid alternative, to the more common procedures to follow sorption experiment in soil matrix samples with no need of sample pre-treatment or column conditioning. This method is much faster and requires less sample manipulation than traditional analytical separation methods Moreover, most modern spreadsheet-applications, such as Excel, now include statistical packages that allow performing multi-linear regression, which make this approach particularly inexpensive since the only requirement is a UV spectrometer. The regression output was made using the Microsoft Excel, a very easy and fast program, allowing anyone, with less knowledge about complex statistical programs. to perform the UV spectral. (C) 2010 Elsevier B.V. All rights reserved